2012
DOI: 10.1111/j.1741-4369.2011.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivating and improving attitudes to reading in the final years of primary schooling in five New Zealand schools

Abstract: Teachers are influential in motivating and improving attitudes towards reading. This article reports on an investigation of eight teachers of 10‐ to 12‐year‐old students from five New Zealand schools and the strategies they used to improve attitudes to reading. Each school had been identified as implementing effective reading programmes by a panel of literacy experts and supported by standardised tests demonstrating overall improvements in reading achievement. A reading culture developed by using sophisticated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…The qualitative data for this study came from interviews with two teachers about the efforts they were making to teach reading comprehension. The main instrument for this study was the interview guide with questions adapted from Fletcher, et al (2012); they focused on curriculum, teaching preparation, teaching methodology, teaching instruction, authentic teaching materials, and perceptions of the teachers towards the reading attitudes of the learners, barriers in teaching reading, and teaching strategies for poor readers. This study used three key stages to analyse the data namely, data reduction, data display and conclusion verification (Miles & Huberman, 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative data for this study came from interviews with two teachers about the efforts they were making to teach reading comprehension. The main instrument for this study was the interview guide with questions adapted from Fletcher, et al (2012); they focused on curriculum, teaching preparation, teaching methodology, teaching instruction, authentic teaching materials, and perceptions of the teachers towards the reading attitudes of the learners, barriers in teaching reading, and teaching strategies for poor readers. This study used three key stages to analyse the data namely, data reduction, data display and conclusion verification (Miles & Huberman, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…There are several aspects of efforts that teachers can do to assist students to improve their reading skills. Fletcher, et al (2012) state that they can be done via: (i) the curriculum used in teaching reading, (ii) their preparations for teaching, (iii) proper methods of teaching, (iv) proper instructions, (v) authentic materials, (vi) the perception of the teachers toward the reading attitudes of their students, (vii) barriers in teaching reading and (viii) teaching strategies for poor readers.…”
Section: Teachers' Efforts In Teaching Readingmentioning
confidence: 99%
“…For over 30 years reading, researchers have found that motivated students are more likely to read and hence over time encounter a greater volume of words in successive consumption of texts. This ‘Matthew effect’ acts through a reciprocal causality between reading frequency, volume and reading skill, producing higher academic attainment in ‘good’ readers; in turn, such readers are more likely to read independently at home and be placed in ‘higher‐ability’ sets at school (Cunningham and Stanovich, ; Fletcher et al, ; Stanovich, ). Conversely, poorer readers who typically come from poorer socio‐economic backgrounds and placed in ‘low‐ability’ sets taught by the least well‐qualified teachers are more likely to practise discrete reading skills on extracts or simplified readers (Allen, ; Dunne and Gazeley, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Duncan () points out that, historically, reading aloud was the dominant form in adult literacy and is still practised widely today for learning, preaching, remembering and understanding, as Brice Heath (, ) found in her seminal studies of socially situated reading practices amongst different communities in the southern states of America. Fletcher et al (, p. 14), in a study of effective reading teachers in New Zealand elementary schools, found that a “particularly successful strategy” was teachers' daily expressive reading aloud to the whole class. Kuhn et al () argue that fluency or automaticity of oral reading improves four skills of speed, effortlessness, autonomy and lack of conscious awareness, all strongly supporting comprehension.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It may be the case that, in eighth grade, academic achievement does not strongly impact self-concept. As Fletcher, Grimley, Greenwood, and Parkhill (2012) suggested, reading may not be considered 'cool' in adolescence. Other factors, which were not investigated in the current study, such as success and participation in athletics, outgoing personality, or fashion, may be more important for self-concept in adolescence.…”
Section: Emotional Engagementmentioning
confidence: 99%